Infinite Element Method for the Exterior Problems of the Helmholtz Equations (Journal of Computational Mathematics, 2021)
There are two cases of the exterior problems of the Helmholtz equation. If λ≥0 the bilinear form is coercive, and if λ＜0 it is the scattering problem. We give a new approach of the infinite element method, which enables us to solve these exterior problems as well as corner problems. A numerical example of the scattering problem is given.